Group Investigation Model Through Concept Maps on Mathematical Problem Solving Ability and Self-Efficaciousness - Kurniawan, Hendra Listya; Mustadi , Ali; Nugroho, Ikhlasul Ardi; Danuri , Danuri (UNNES JOURNAL, 2024)
Problem-solving abilities are often associated with student self-efficacy. This is important because it is one of the mathematics learning goals that students must achieve. Based on a preliminary study through observation, documentation, and interviews with basic mathematics education lecturers at one of the non-state universities in Yogyakarta, it shows that students' mathematical problem-solving abilities and self-efficacy are not yet optimal. Development research was carried out with an investigative group through concept maps using the Dick and Carey model. The results of the effectiveness test on 33 basic education students at PGRI Yogyakarta University showed a significant increase in problem-solving abilities and self-efficacy, so it can be concluded that the development of an investigative group learning model is very valid and feasible to implement. It is hoped that this research can become a reference for the application of cooperative learning by lecturers at other universities. Kemampuan pemecahan masalah sering dikaitkan dengan self-efficacy peserta didik. Hal tersebut penting karena merupakan salah satu tujuan pembelajaran matematika yang harus dicapai oleh peserta didik. Namun, berdasarkan studi pendahuluan melalui observasi, dokumentasi, dan wawancara dengan dosen mata kuliah Matematika 2 Program Studi Pendidikan Guru Sekolah Dasar salah satu perguruan tingi swasta di Yogyakarta menunjukkan belum optimalnya kemampuan pemecahan masalah matematis dan self-efficacy mahasiswa. Penelitian pengembangan dilakukan dengan grup investigasi melalui peta konsep menggunakan model Dick and Carey. Draf perangkat pembelajaran grup investigasi divalidasi oleh dua ahli dan satu user, menunjukkan kriteria valid dan layak digunakan. Hasil uji efektivitas terhadap 33 mahasiswa Program Studi Pendidikan Guru Sekolah Dasar Universitas PGRI Yogyakarta menunjukkan terdapat peningkatan signifikan pada kemampuan pemecahan masalah dan self-efficacy sehingga dapat disimpulkan pengembangan model pembelajaran grup investigasi sangat valid dan layak diterapkan. Penelitian ini diharapkan menjadi referensi penerapan pembelajaran kooperatif oleh dosen di perguruan tinggi lain.